Examining the Effects of Biochar in Spinach Cultivation with Increased Irrigation Water Salinity on Some Physical and Physiological Properties of the Plant - Yerli, Caner (International Conference on Applied Engineering and Natural Sciences, 2023)
The inadequacy of fresh water resources in today's conditions has revealed the use of salty water as an alternative water source in agricultural irrigation but salinity, which is shown as the most important source of abiotic stress, increases osmotic stress and decreases the water intake of the plant, resulting in a physiological drought. For this reason, there is a need for applications to improve the decreasing efficiency in the use of salt water in irrigation through different practical and economic approaches. This study investigating the effects of biochar application into the soil against irrigation water salinity in spinach cultivation on some physical and physiological properties of the plant was carried out in five-liter pots in greenhouse conditions, in a completely randomized factorial experimental design with three replications, in three different irrigation water salinity levels with NaCl salt source [I0: tap water; 0.4 (control), I1: 2.5, I2: 5 dS m-1 ] and three different biochar dosage based on weight [B0: 0 (control), B1: 1.5, B2: 3%] conditions. As a result of the study, plant height, leaf number and area, shoot wet weight from physical properties and chlorophyll and leaf relative water contents from physiological properties decreased with increasing irrigation water salinity levels but the membrane damage decreased, while the physical and physiological properties of spinach increased with the increasing mixing ratio of biochar to the soil, excluding membrane damage. It was found that the use of biochar against irrigation water salinity can be recommended considering that mixing biochar to the soil against irrigation water salinity in spinach cultivation regulates the physical and physiological properties of the plant but to obtain more comprehensive information on this subject, evaluation of different irrigation water salinity and biochar ratios in terms of field studies has emerged as a recommendable result.